The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.5194/nhess-9-1931-2009
|View full text |Cite
|
Sign up to set email alerts
|

Taking the heterogeneity of citizens into account: flood risk communication in coastal cities – a case study of Bremen

Abstract: Abstract. The likely manifestations of climate change like flood hazards are prominent topics in public communication. This can be shown by media analysis and questionnaire data. However, in the case of flood risks an information gap remains resulting in misinformed citizens who probably will not perform the necessary protective actions when an emergency occurs. This paper examines more closely a newly developed approach to flood risk communication that takes the heterogeneity of citizens into account and aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 15 publications
3
37
0
3
Order By: Relevance
“…This rationale is still common in risk communication. In a review of risk communication strategies in Europe, Höppner et al (2012) revealed a gap between practice, which tends to follow traditional approaches, and recent research, which recommends two-way communication and more deliberative approaches tailored to the needs of the population (Renn, 2008;Martens et al, 2009). However, the effort required by dialogue-based strategies often seems very high to practitioners.…”
Section: Relevant Findings and Open Research Questions On Risk Preparmentioning
confidence: 99%
“…This rationale is still common in risk communication. In a review of risk communication strategies in Europe, Höppner et al (2012) revealed a gap between practice, which tends to follow traditional approaches, and recent research, which recommends two-way communication and more deliberative approaches tailored to the needs of the population (Renn, 2008;Martens et al, 2009). However, the effort required by dialogue-based strategies often seems very high to practitioners.…”
Section: Relevant Findings and Open Research Questions On Risk Preparmentioning
confidence: 99%
“…Above all, issues surrounding flood risk management are seen in the region in relation to the disastrous floods of 1962 (especially in Hamburg); often the flood disasters, which affected the hinterland in 2002, are also quoted (next case study). Moreover, studies have revealed that climate change receives relatively high coverage in the regional media (Martens et al 2009) and that it is often the subject of controversial debates both within and outside the regional parliament Germanwatch 2009). The interviews point to the publication of the IPCC Report 2007 as an decisive contributing factor to the genesis of the Generalplan Küstenschutz, which ultimately forced existing skepticism concerning the urgency of policies of adaptation to climate change on the defensive and triggered pressure for political action on the regional level.…”
Section: Case Studies: German Adaptation Policies In the Realm Of Flomentioning
confidence: 99%
“…At the other, a failure by the public to simply comprehend received information is problematic (Twigger-Ross et al, 2009a;Du Plessis, 2002;Faulkner et al, 2007). Distrust and low confidence levels in the authorities that provide information (Basher, 2006;Renn and Levine, 1991), sometimes compounded by misleading or contradictory information reported in national and local media, can also serve to diminish the public response to flood risks (Martens et al, 2009;United Nations, 2006;Miles and Morse, 2007). Any or a combination of these factors may potentially contribute to the public being poorly informed of a flood risk with the consequence that the opportunity for…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for failed communications are diverse. At one end of the spectrum, the complex social dynamic between government, responsible authorities and the public at large is at the forefront of the decision making process and in some instances, the political and social consequences of conveying the risk directs the communication process (Terpstra et al, 2009;Martens et al, 2009;United Nations, 2006). At the other, a failure by the public to simply comprehend received information is problematic (Twigger-Ross et al, 2009a;Du Plessis, 2002;Faulkner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%